Ventricular Septal Defect Following Blunt Chest Trauma in Child: Case Report - El haddaji, Anass; Elkhettab, F.; Zidouh, A.; Merbouh, M.; Sahraoui, H.; Mouaffek, Y.; Younous, S. (International Journal of Innovative Research in Medical Science, 2024)
Blunt thoracic trauma can lead to cardiac injuries such as myocardial contusion and valvular damage, but the occurrence of traumatic ventricular septal rupture is an exceptionally rare complication, especially in infants. We present an unusual case of an infant who sustained a ventricular septal rupture following blunt thoracic trauma, necessitating surgical repair. The proposed mechanism involves acute compression of the infant's heart between the sternum and vertebral column during ventricular filling, leading to a rapid intraventricular pressure spike that may rupture the interventricular septum. Our findings underscore the importance of prompt surgical intervention for large septal defects and hemodynamic instability arising from such traumatic cardiac injuries, even in infants. Early recognition and timely operative management are crucial for improved outcomes in these rare but life-threatening pediatric cases. We discuss the clinical presentation, diagnostic approach, and surgical treatment of this exceptional condition in an infant, contributing to the limited body of knowledge on this topic.